Consolidation, Fragmentation, and the Disclosure of Trading Information - Madhavan, Ananth (Review of Financial Studies, 1995)
Journal Article Consolidation, Fragmentation, and the Disclosure of Trading Information Get access Ananth Madhavan Ananth Madhavan University of Southern California Address all correspondence to Ananth Madhavan, School of Business Administration, University of Southern California, Los Angeles, CA 90089-1421. Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 8, Issue 3, July 1995, Pages 579–603, https://doi.org/10.1093/rfs/8.3.579 Published: 28 May 2015